A Comparative Study of the Glandular Trichomes on the Upper and Lower Leaf Surfaces of Origanum x intercedens Rech - Bosabalidis, A. M.; Skoula, M.
Microscopic, distributional and chromatographic procedures were employed to characterize glandular trichomes on the leaves of Origanum x intercedens. Microscopic examination of first-expanded leaves showed that peltate glandular trichomes are seated on flat epidermis, are densely arranged and occur at different developmental stages. In fully-expanded leaves, glandular trichomes are seated in local depressions of the epidermis, are thinly arranged and occur only at advanced developmental state. On the upper epidermis of fully-grown leaves, glandular trichomes are more numerous and with larger oil-bearing subcuticular spaces compared to those on the lower. They are about evenly distributed over the entire surface of the lamina. Stomata occur on both epidermal surfaces, but their number is 13-fold greater on the lower epidermis. Correlation of the patterns of glandular trichome arrangement on the upper and lower leaf sides in order to estimate whether there is a possible correspondence in the positions of the glandular trichomes, disclosed that the frequencies of trichome proximity follow approximately a normal distribution. GC/MS analyses of the essential oils separately derived from the populations of glandular trichomes on the upper and lower leaf surfaces showed that the oils differ slightly in qualitative and quantitative composition. The ecological significance of glandular trichomes on the leaf of O. x intercedens is thought to be mainly associated with protection from UV-radiation and insect attack.
Keywords: ORIGANUM X INTERCEDENS; LABIATAE; GLANDULAR TRICHOMES; LEAF SURFACES; ESSENTIAL OIL COMPOSITION